2000
DOI: 10.1176/appi.ajp.157.9.1504
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of the Stimulus Characteristics of ECT

Abstract: The pulse width of 0.5 msec is more efficient than the 1-msec pulse width. The "half-age" dose for the first bilateral ECT treatment is usually successful for subsequent ECTs when the 0.5-msec pulse width is used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 8 publications
1
19
0
Order By: Relevance
“…A study by Swartz and Larson suggests that stimulus frequency of 60 pps was more efficient than 120 pps at inducing seizures (BL placement, bidirectional, amplitude = 800 mA, PW = 1.5 ms, 120 pulses) 17. However, a similar study found no difference in seizure induction efficiency between 60 pps and 120 pps frequency (LART placement, bidirectional, amplitude = 900 mA, PW = 0.5 ms and 1 ms, charge = 2.27 mC per patient’s year of age) 18. Devanand et al showed that the seizure threshold is lower when titrated by stimulus duration (0.5–4 s) than when titrated by frequency (40–280 pps) with BL ECT (bidirectional, amplitude = 800 mA, PW = 1 ms),19 supporting the view that lower frequencies are more efficient.…”
Section: Understanding the Ect Stimulus Parametersmentioning
confidence: 94%
See 1 more Smart Citation
“…A study by Swartz and Larson suggests that stimulus frequency of 60 pps was more efficient than 120 pps at inducing seizures (BL placement, bidirectional, amplitude = 800 mA, PW = 1.5 ms, 120 pulses) 17. However, a similar study found no difference in seizure induction efficiency between 60 pps and 120 pps frequency (LART placement, bidirectional, amplitude = 900 mA, PW = 0.5 ms and 1 ms, charge = 2.27 mC per patient’s year of age) 18. Devanand et al showed that the seizure threshold is lower when titrated by stimulus duration (0.5–4 s) than when titrated by frequency (40–280 pps) with BL ECT (bidirectional, amplitude = 800 mA, PW = 1 ms),19 supporting the view that lower frequencies are more efficient.…”
Section: Understanding the Ect Stimulus Parametersmentioning
confidence: 94%
“…2, but the biological action of these different combinations can be quite distinct. For example, Swartz et al showed that for fixed total stimulus charge, seizures are induced with a significantly higher success rate with briefer versus longer pulse widths 17,18. In these studies the briefer pulse width trains contained twice as many pulses as the longer pulse width trains in order to maintain fixed charge.…”
Section: Present State Of the Art Of Ect Dosingmentioning
confidence: 99%
“…Charge rates could influence stimulus efficiency. 4 Constant charge rates across the 2 groups as far as possible potentially eliminated the systematic bias of variation in efficacy outcomes. Thus, it was possible to ''isolate'' the 2 pulse widths and study their differences.…”
Section: Discussionmentioning
confidence: 99%
“…Third, 6 times the threshold dose is a ''markedly suprathreshold dose'' and with unilateral brief pulse ECT matches the antidepressant efficacy of bilateral ECT but with lesser degree of cognitive adverse effects. 4 This study has therefore compared ultrabrief pulse unilateral ECT to perhaps the criterion-standard brief pulse unilateral ECT treatment. Fourth, double-blind assessment of outcome was carried out at an identical time point (24 hours after the eighth treatment).…”
Section: Discussionmentioning
confidence: 99%
“…The relative importance of these parameters is still insufficiently understood, but in the interval, 30-60 Hz frequency proved unimportant (42). Stimulation for 2 s compared to 1 s with the same dose of electricity was more efficient (43).…”
Section: Seizure Inductionmentioning
confidence: 99%